Comparing the effectiveness of selective laser trabeculoplasty with topical medication as initial treatment (the Glaucoma Initial Treatment Study): Study protocol for a randomised controlled trial - Lamoureux E.L. (BioMed Central Ltd., 2018)
10.1186/s13063-015-0924-6